Decision Support System for PKH Assistance Recipients Promethee Method - Alifcha Ghazian; Yuhandri; Muhammad Ikhlas (Universitas Putra Indonesia YPTK Padang, 2023)
The Family Hope Program (PKH) is a program providing conditional social assistance to Beneficiary Families (KPM) who are designated as PKH beneficiary families. With the current development of information technology, decision making can be assisted by using computers equipped with application programs to support the production of the required quality decisions. In selecting families who receive assistance from the Family Hope Program (PKH) using the Decision Support System using the Promethee method. Promethee is a method of determining the order (priority) in multi-criteria analysis, the result of this method is a ranking of alternatives based on the selected criteria. The decision support system application using the Promethee method can determine which disadvantaged families will receive PKH assistance with faster, more accurate and fair calculations and considerations. The results of research using this method using 5 alternatives, there are 3 alternatives with accepted status and 2 alternatives that are rejected. The accepted alternatives were Tiah, Mansyah and Mus Muliadi. Meanwhile, the alternatives that were rejected were Irmansyah and Ainun. By obtaining calculation results from a decision support system using the Promethee method, it can help and make it easier for sub-districts to determine recipients of the Family Hope Program (PKH) for underprivileged families.